2002
DOI: 10.1021/ja026568k
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Catalytic Asymmetric Addition of Alkyl Groups to Ketones

Abstract: Many catalysts will promote the asymmetric addition of alkylzinc reagents to aldehydes. In contrast, there are no reports of additions to ketones that are both general and highly enantioselective. We describe herein a practical catalytic asymmetric addition of ethyl groups to ketones. The catalyst is derived from reaction of camphor sulfonyl chloride and trans-1,2-diaminocyclohexane. The resulting diketone is reduced with NaBH4 to give the C2-symmetric exo diastereomer. Use of this ligand with titanium tetrais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
68
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(68 citation statements)
references
References 14 publications
0
68
0
Order By: Relevance
“…We have examined the use of our bis(sulfonamide) diol ligand (1) in the asymmetric addition of phenyl groups to cyclic ␣,␤-unsaturated ketones. Good to excellent enantioselectivities have been obtained with cyclic enones bearing alkyl substituents in the 2 position (71-97% enantiomeric excess).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We have examined the use of our bis(sulfonamide) diol ligand (1) in the asymmetric addition of phenyl groups to cyclic ␣,␤-unsaturated ketones. Good to excellent enantioselectivities have been obtained with cyclic enones bearing alkyl substituents in the 2 position (71-97% enantiomeric excess).…”
mentioning
confidence: 99%
“…1; ref. 1). When cyclic ␣,␤-unsaturated ketones were used as substrates, we found that the asymmetric addition reaction could be coupled with a diastereoselective epoxidation by using molecular oxygen as the oxidant to provide a one-pot synthesis of epoxy alcohols with high enantio-and diastereoselectivity (Eq.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 Walsh and co-workers described also the synthesis of tertiary alcohols by the asymmetric addition of ZnEt 2 to ketones catalyzed by a titanium catalyst with a chiral diamine ligand. 5 (B) 1,4-Addition to Cyclic Enones: Alexakis and co-workers reported an asymmetric copper-catalyzed 1,4-addition of diethylzinc to cyclic enones using a phosphoramidite ligand, followed by C-enolate trapping resulting in the synthesis of α,β-disubstituted ketones with a high degree of stereoselectivity. 6 (C) 1,4-Addition to Reactive Acceptors: Carreira and co-workers developed the copper-catalyzed highly stereoselective conjugate addition of diethylzinc to Meldrum's acid derived acceptors with phosphoramidite ligands.…”
Section: Abstractsmentioning
confidence: 99%
“…This reaction was studied by Walsh et al using bis(sulfonamido) or BINOL/ Ti(i-PrO) 4 complexes, applied to aldehydes, 17 ketones 18 and a,b-unsaturated ketones. 19 In the case of 18, the reaction is totally chemoselective, as no conjugate addition compound was detected.…”
Section: Introductionmentioning
confidence: 99%